The Effect of Sevoflurane Anesthesia on the Biomarkers of Neural Injury in the Prefrontal Cortex of Aged Marmosets - Cheng, Yanyong; Shi, Lingling; Mao, Haoli; Xue, Zhenyu; Liu, Siyu; Qiu, Zilong; Zhang, Lei; Jiang, Hong (Frontiers in Aging Neuroscience, 2022)
Background: Previous studies have suggested that older patients undergoing surgery under anesthesia could be at an increased risk for the neural injury. Sevoflurane anesthesia without surgery for 2 h does not induce neural injury, however, whether prolonger sevoflurane anesthesia without surgery induces it is still unknown. Methods: In present study, marmosets were exposed at clinical concentration of sevoflurane (1.5% to 2%) for 6 h to access the effects of sevoflurane anesthesia on the levels of IL-6 and TNF-α, Caspase3 activity and myelin formation in brain tissues. Results: Sevoflurane anesthesia did not alter the expression of IL-6 (120.1±2.21 vs. 120.8±2.25, p = 0.74), TNF-α (189.3±31.35 vs. 218.7±21.47, p = 0.25) and Caspase3 (57.35±1.54 vs. 58.67±1.19, p = 0.53) in the prefrontal cortex of aged marmosets. The amount of MBP expression (60.99±6.21 vs. 58.91±2.71, p = 0.77) did not change upon sevoflurane exposure. Conclusion: Sevoflurane anesthesia did not increase the levels of IL-6 and TNF-α, activated the expression of Caspase3 and induced myelination deficits in the prefrontal cortex of aged marmosets.